Clinical manifestation of an amelanotic Sporothrix schenckii complex isolate in a cat in Germany. Issue 4 (August 2015) - Scheufen, Sandra; Strommer, Sellyn; Weisenborn, Jascha; Prenger-Berninghoff, Ellen; Thom, Nina; Bauer, Natali; Köhler, Kernt; Ewers, Christa
Abstract : Introduction: Dimorphic fungi of the Sporothrix schenckii complex are the aetiological agent of sporotrichosis in humans and animals. Cats in particular have gained importance in transmission of the disease to humans. Therefore, it is crucial to identify unusual aetiological agents and the varying clinical appearances of the disease. Case presentation: We describe the case of a 10-year-old cat with a 2-month history of nasal discharge after a fight with another cat. Severe thrombocytopenia was diagnosed, whilst routine testing for feline leukemia virus (FeLV) was negative. A computed tomography scan revealed profound destruction of several parts of the nasal cavity. Histological and cytological examination of biopsies taken from these locations showed a chronic pyogranulomatous inflammation with several yeast-like structures. Mycological cultivation at 28 and 37 °C yielded fungal growth with smooth to wrinkled colonies consisting of hyphae and non-pigmented sympodial, round to oval-shaped conidia. Molecular typing, including sequence analysis of the ITS region, resulted in a consensus sequence which allowed classification of the fungus into the Sporothrix schenckii complex. Although the thrombocytopenia persisted, treatment with itraconazole dissolved any respiratory symptoms and improved the clinical status of the cat, indicating an antimycotic-responsive infection. Conclusion: Amelanotic members of the Sporothrix schenckii complex should be considered a putative aetiologic agent in the pathogenesis of feline sporotrichosis in Germany. Besides being classified in close proximity to species in the environmental clade this isolate has proven to cause serious infection implying a possible zoonotic potential.